Backcasting Finnish energy and forest sector futures to meet the EU Green Deal in 2050 : Normative Scenario development for Finnish energy and forestry sector to understand the business and regulatory environment of the European Union Green Deal climate targets in 2050 - Wahlberg, Satu (My University, 2024)
The discourse on sustainability transition has gathered global attention, with pressing issues like climate change, global warming, and biodiversity losses prompting a call to action. While corporate strategies today state to prioritize sustainability, actual implementation falls short, with a focus on incremental rather than transformative change. Understanding the effects of regulatory environment, market dynamics, and technological development on sustainability transformation aligns corporate actions providing an understanding of how large-scale complex transformation can be enabled. In Finland energy and forest sectors present two large industries, whose emissions and carbon storage capabilities affect the EU Green Deal and thus national climate goals. These two sectors represent two sides of the coin. Where the energy sector is urging to cut down greenhouse gas emissions, the forest sector needs to act in increasing the natural carbon storage. Fostering a climate-neutral economy is the key goal of the EU Green Deal. The long-term goal of being the first climate-neutral continent by 2050 provides many ambitious sub-targets to EU countries and their industries. The emission-cutting plan has been divided into three middle points: in 2030 EU net emissions should be reduced by 55% compared to the year 1990, in 2040 the emissions should be decreased by 90% and in 2050 the goal is to be climate neutral. The EU Green Deal guides Finnish climate politics and thus also Finnish energy and forest sectors. The goal of the research is to understand how the EU Green Deal targets could be reached in certain industries. To understand alternative possible routes to reach the target I used normative scenarios to illustrate the possible futures of net-zero economy. Normative scenarios and backcasting techniques provide answers to "How can a certain future be reached?". In this research, this question is relevant, as the long-term goal is set. The empirical part of the research consists of qualitative research in which I interviewed a total of nine experts in the fields of energy and forestry. These experts represent various perspectives: political, economic, social, technological, and environmental. Based on the research interviews the understanding of the dynamics of a socio-technical transformation was seen. The scenarios are created from three perspectives: regulation-driven change, market-driven change, and technology-driven change. Where the regulatory environment is pushing the change towards a climate-neutral economy, the transformation is not possible without market development and technological innovations. These three combine a landscape for the large-scale sustainability transformation.

Keskustelu kestävän kehityksen siirtymästä on saanut laajaa huomiota, kun kiireelliset ilmiöt, kuten ilmastonmuutos, maailmanlaajuinen ilmaston lämpeneminen ja luontokato ovat kannustaneet toimimaan kestävästi. Vaikka yritysten strategiat tänään kertovat kestävyyden olevan tärkeää, jää toteutus vaillinaiseksi, kun yritykset keskittyvät ennemmin pikemminkin inkrementaaliseen kuin transformatiiviseen muutokseen. Regulaation, markkinadynamiikan ja teknologisen kehityksen vaikutusten ymmärtäminen kestävyysmuutoksen edessä tarjoaa näkemystä siitä, miten suuria monimutkaisia muutoksia voidaan mahdollistaa. Suomen energia- ja metsäsektorit edustavat kahta suurta teollisuutta, joiden sekä päästöt että hiilen sidontakyky vaikuttavat EU:n ilmastotavoitteisiin ja siten kansallisiin ilmastotavoitteisiin. Nämä kaksi sektoria edustavat kolikon kahta puolta – energia-ala painottaa kasvihuonekaasupäästöjen vähentämistä, kun taas metsäalalla kriittistä on hiilensidonta luonnon monimuotoisuusarvot toteuttaen. Hiilineutraalin talouden edistäminen on EU Green Deal -paketin keskeinen tavoite. Pitkän aikavälin tavoite on olla ensimmäinen päästöneutraali maanosa vuoteen 2050 mennessä. Tämä asettaa monia kunnianhimoisia alatavoitteita EU-maille ja niiden teollisuudelle. Päästöjenvähennysstrategia on jaettu kolmeen välietappiin: vuoteen 2030 mennessä EU:n nettomääräisten päästöjen on vähennyttävä 55 % vuoden 1990 tasosta, vuoteen 2040 mennessä päästöjen on vähennyttävä 90 % ja vuoteen 2050 mennessä tavoitteena on olla hiilineutraali. EU Green Deal ja ilmastolaki ohjaavat Suomen ilmastopolitiikkaa ja siten myös suomalaisia energia- ja metsäsektoreita. Tutkimuksen tavoitteena on ymmärtää, miten EU Green Deal -sopimuksen tavoitteisiin voitaisiin päästä näillä aloilla. Ymmärtääkseen vaihtoehtoisia mahdollisia reittejä tavoitteen saavuttamiseksi käytin normatiivisia skenaarioita kuvatakseni mahdollisia tulevaisuuksia ilmastoneutraalille taloudelle. Normatiiviset skenaariot ja backcasting-menetelmä antavat vastauksia kysymykseen "Miten tietty tulevaisuus voidaan saavuttaa?". Tässä tutkimuksessa kysymys on relevantti, kun pitkän aikavälin tavoite vuoteen 2050 on asetettu. Tutkimuksen empiirinen osa koostuu laadullisesta tutkimuksesta, jossa haastattelin yhteensä yhdeksää asiantuntijaa energia- ja metsäaloilta. Nämä asiantuntijat edustavat eri näkökulmia: poliittisia, taloudellisia, sosiaalisia, teknologisia ja ympäristöön liittyviä. Tutkimushaastatteluiden perusteella saatiin näkemyksiä sosioteknisen muutoksen dynamiikasta. Skenaariot luotiin kolmesta näkökulmasta: regulaatioon perustuva muutos, markkiavetoinen muutos ja teknologiapohjainen muutos. Siinä missä egulaatio työntää muutosta kohti ilmastoneutraaliutta, ei muutos ole mahdollinen ilman markkinoiden kehitystä tai teknologisia innovaatioita. Nämä kolme yhdessä luovat kehyksen laajamittaisen kestävyysmuutoksen onnistumiselle.
Keywords: EU Green Deal, Sustainable Development, Normative Scenarios, Energy Sector, Forest sector, kestävä kehitys, normatiiviset skenaariot, energiasektori, metsäsektori